Enhancing strength capacity for triathlon competitors - Marica, A. V.; Stoica, M.; Dreve, A. A. (Physical Education, Sport and Kinetotherapy Journal, 2024)
Triathlon is a sport that combines three different disciplines: swimming, cycling and running. Athletes have to cover varying distances in each discipline and move quickly from one to the next, making triathlon an extremely demanding sport. This research aims to develop and implement a training program with athletic means in order to optimize the strength capacity of triathletes. This papersought to identify statistically significant differences between the results recorded by the participants, i.e. the performance of athletes at the beginning and end of the study, following an experimental intervention. The present research was carried out with the participation of 3 male athletes, aged between 20 and 36 years (m = 26), from the triathlon sports branch, with over 4 years of competitive experience, competitor in the National Championship. Strength evaluation was conducted using the Optojump system in the case of the participants who performed one test: Left and Right Leg Jumps (5 jumps). Statistical analysis using the Wilcoxon signed-rank test showed significant differences between the initial and final results for explosive strength, indicating that the improvements were not random but were due to the experimental intervention. The training program had a significantly positive impact on the participants' strength capacity and overall performance.